Musculoskeletal diseases in forestry workers - Vuković Slađana; Krstev Srmena; Maksimović Miloš Ž. (Srpski Arhiv za Celokupno Lekarstvo, 2004)
The most common hazards in the forestry that may induce disorders of the musculoskeletal system are vibrations, unfavorable microclimatic conditions, noise, over-time working hours, work load and long-term repeated movements. The objective of this study was to analyze the prevalence of musculoskeletal diseases and its difference among workers engaged in various jobs in the forestry. Two groups of workers were selected: woodcutters operating with chain-saw (N=33) and other loggers (N=32). Selected workers were of the similar age and had similar total length of employment as well as the length of service in the forestry. Both groups of workers employed in the forestry had the high prevalence of musculoskeletal diseases (woodcutters 69.7% and other loggers 62.5%, respectively). Degenerative diseases of spinal column were very frequent, in dependently of the type of activity in the forestry. Non-significantly higher risk of carpal tunnel syndrome was found in woodcutters with chain-saw compared to workers having other jobs in the forestry (OR=3.09; 95%CI=0.64-19.72). The lateral epicondylitis was found only in woodcutters operating with chain-saw with the prevalence of 18.2%.